Peran Tax Planning dan Konsultan Pajak - Willi Fatimaleha; Anna Sofia Atichasari; Eso Hernawan; Ni’matullah Ni’matullah (STATERA: Jurnal Akuntansi dan Keuangan, 2020)
The study aims to examine the influence of tax planning, and tax consultants on compliance with corporate income tax payments. The sample in this study were 60 respondents with a sampling technique with a purposive sampling method that is by determining certain criteria according to research needs with corporate taxpayers registered in the Tax Office one large taxpayer Jakarta as the respondent. Data was collected by distributing questionnaires directly to the respondents concerned. The analytical method used in this study is the analysis of Multiple Regression. The data in this study were processed using SPSS version 25 software (Statistical Product and Service Solution). The results of this study indicate that tax planning and tax consultants have a positive and significant effect on compliance with corporate income tax payments.